Belief, Prejudice dan Diskriminasi - Gazi Saloom (‎‎‎TAZKIYA Journal of Psychology, 2003)
Book title : Group Beliefs: A Concption for Analyzing Group Structure, Process and BehaviorWriter : Daniel Bar-TalPublisher : Springer Verlag New York, 1989